STUDI KASUS IMPLEMENTASI METODE BLOCKING PORT DALAM PENCEGAHAN MALWARE - Cosmas Eko Suharyanto; Pastima Simanjuntak (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2023)
Computer networks have become a staple in various fields. connected to the internet will increase the likelihood of threats or disruption to system security. Malicious Software (malware) is a program that is created with the aim of finding weaknesses or even damaging software and computer operating systems, they can enter through open ports that are not used in the network. After the author made observations at the XYZ School and conducted literature studies from various sources, the Router Mikrotik was needed to prevent this and the Dionaea Honeypot as a malware detection tool on the local network. This study aims to build a computer network security system with blocking port method at XYZ School by using observation, literature study and analysis methods. After the completion of this research, the security system of the XYZ School network can maximize system performance, prevent the entry of Malicious Software (malware).